Detection of malignancy-associated phosphoproteome changes in human colorectal cancer induced by cell surface binding of growth-inhibitory galectin-4 - Michalak, Malwina; Warnken, Uwe; Schnölzer, Martina; Gabius, Hans-Joachim; Kopitz, Jürgen (IUBMB life, 2019)
Emerging evidence on efficient tumor growth regulation by endogenous lectins directs interest to determine on a proof-of-principle level the range of information on alterations provided by full-scale analysis using phosphoproteomics. In our pilot study, we tested galectin-4 (gal-4) that is a growth inhibitor for colon cancer cells (CRC), here working with the LS 180 line. In order to cover monitoring of short- and long-term effects stable isotope labeling by amino acids in cell culture-based quantitative phosphoproteomic analyses were conducted on LS 180 cell preparations collected 1 and 72 h after adding gal-4 to the culture medium. After short-term treatment, 981 phosphosites, all of them S/T based, were detected by phosphoproteomics. Changes higher than 1.5-fold were seen for eight sites in seven proteins. Most affected were the BET1 homolog (BET1), whose level of phosphorylation at S50 was about threefold reduced, and centromere protein F (CENPF), extent of phosphorylation at S3119 doubling in gal-4-treated cells. Phosphoproteome analysis after 72 h of treatment revealed marked changes at 33 S/T-based phosphosites from 29 proteins. Prominent increase of phosphorylation was observed for cofilin-1 at position S3. Extent of phosphorylation of the glutamine transporter SLC1A5 at position S503 was decreased by a factor of 3. Altered phosphorylation of BET1, CENPF, and cofilin-1 as well as a significant effect of gal-4 treatment on glutamine uptake by cells were substantiated by independent methods in the Vaco 432, Colo 205, CX 1, and HCT 116 cell lines. With the example of gal-4 which functions as a tumor suppressor in CRC cells, we were able to prove that cell surface binding of the lectin not only markedly influences the cell proteome, but also has a bearing on malignancy-associated intracellular protein phosphorylation. These results underscore the potential of this approach to give further work on elucidating the details of signaling underlying galectin-triggered growth inhibition a clear direction. © 2018 IUBMB Life, 71(3):364-375, 2019
Published online 14 December 2018
Gesehen am 06.09.2019